2018
DOI: 10.1007/s10953-018-0782-4
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism for Solvent Extraction of Lanthanides from Chloride Media by Basic Extractants

Abstract: The solvent extraction of lanthanides from chloride media to an organic phase containing an anion exchanger in the chloride form is known to show low extraction percentages and small separation factors. The coordination chemistry of the lanthanides in combination with this kind of extractants is poorly understood. Previous work has mainly used solvent extraction based techniques (slope analysis, fittings of the extraction curves) to derive the extraction mechanism of lanthanides from chloride media. In this pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 45 publications
0
20
0
Order By: Relevance
“…Although LiCl only acts as a chloride source to promote extraction of Co­(II) and Sm­(III) (according to eqs and , respectively), TEAC plays different roles for the extraction of Sm­(III) and Co­(II): (1) It acts only as a chloride source for Sm­(III) extraction (according to eq ), but the ammonium cation does not bind with Sm­(III) because Sm­(III) cannot form an anionic chlorometallate complex in ethylene glycol as a result of the low stability of the Sm–Cl complex. , (2) It functions both as a chloride source (when TEAC < 1.2 mol·L –1 , according to eq ) and as a complexing agent in the case of Co­(II) extraction (when TEAC > 1.2 mol·L –1 , according to eq ).…”
Section: Resultsmentioning
confidence: 99%
“…Although LiCl only acts as a chloride source to promote extraction of Co­(II) and Sm­(III) (according to eqs and , respectively), TEAC plays different roles for the extraction of Sm­(III) and Co­(II): (1) It acts only as a chloride source for Sm­(III) extraction (according to eq ), but the ammonium cation does not bind with Sm­(III) because Sm­(III) cannot form an anionic chlorometallate complex in ethylene glycol as a result of the low stability of the Sm–Cl complex. , (2) It functions both as a chloride source (when TEAC < 1.2 mol·L –1 , according to eq ) and as a complexing agent in the case of Co­(II) extraction (when TEAC > 1.2 mol·L –1 , according to eq ).…”
Section: Resultsmentioning
confidence: 99%
“…Dissociation energies ( D e ) were calculated by determining the difference in the electronic energy between the diatomic at its optimized geometry and the energy of the two infinitely separated substituent atoms. The ground-state electronic configurations of the lanthanide ions were taken from ref (assuming the Ln + charge state for the fluorides and Ln 2+ for the oxides). In addition, frequency calculations were performed on optimized geometries to acquire harmonic zero-point vibrational energies (ZPVEs) so that experimental dissociation energies ( D 0 ) could be converted to values directly comparable to the theoretical values.…”
Section: Computational Detailsmentioning
confidence: 99%
“…The size of this market and the criticality of some of the lanthanides in modern technology demand efficient separation. However, because lanthanide cations have similar physicochemical properties, their separation becomes a very challenging task. , Solvent extraction is the most often used separation process; in this process, the slight differences in the properties along the lanthanide series are exploited to allow preferential extraction of specific lanthanides from a mixture using organic-based ligand extractants. …”
Section: Introductionmentioning
confidence: 99%
“…They concluded that an anion exchange mechanism for adsorption on resins was correct, although significant adsorption was already found when only very low concentrations of anionic species were present. , Also, no explanation for the decreasing adsorption efficiency at high HCl concentrations could be given. Onghena et al and Vander Hoogerstraete et al investigated the speciation of trivalent lanthanide ions in solvent extraction systems and concluded that the speciations in the aqueous and organic phase are different. Deferm et al studied the solvent extraction and speciation of In­(III) and related the aqueous In­(III) species to the extraction efficiency of In­(III) .…”
Section: Introductionmentioning
confidence: 99%